The organ music of J.S. Bach - Williams, Peter F. (Cambridge University Press, 2003)
Taking account of Bach scholarship of the past twenty-five years, the first two volumes of Peter Williams's classic study of Bach's organ works are fully revised. This work is a piece-by-piece commentary on this ever-popular repertoire, demonstrating the music's unique qualities and how we might hear and play it today. The book follows the order of the Bach catalog (BWV): beginning with the sonatas, followed by the "free works" and the chorales, and ending with the doubtful works, including the "newly discovered chorales" of 1985